The nursing image and professional identity. The future of a construction - Samaniego, Virginia Corina; Cárcamo, Silvia (Investigación y Educación en Enfermería, 2025)
Objective. This study sought to describe the image nurses, physicians, and other healthcare professionals have of nurses. Methodology. We performed a descriptive study conducted in 2010 on a probabilistic sample of 308 participants (100 nurses, 103 physicians, and 105 other professionals) from Buenos Aires, Argentina. The study used questionnaires with multiple choice closed questions. Results. Among the main results, we found a perception of the working conditions that imply wear, helplessness, and conflicts within the work group with greater frequency among nurses than in other study groups. Likewise, discrepancies were found between what nurses and the rest of professionals consider 'specific nursing functions'. Conclusion. Tension exists between the role prescribed by the medical model and that defined by nursing. It is necessary to conceive how the professional identity is constructed as of identifying strategies resulting from objective and subjective strategies.